Factors Associated With Chlamydia and Gonorrhea Treatment Completion Among Sexual Health Clinic Patients, Baltimore City, Maryland; 2018 to 2019 - Stracker, Norberth; Williford, Sarah L; Gilliams, Elizabeth; Rives, Sarah; Page, Kathleen R; Hamill, Matthew M; Greenbaum, Adena; Schumacher, Christina M (Sexually transmitted diseases, 2023)
Prompt and appropriate treatment of Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) is critical to prevent transmission and serious sequelae. The objectives were to determine the prevalence of CT/NG treatment completion and identify demographic, behavioral, and clinical factors associated with treatment completion at sexual health clinics in Baltimore City, Maryland. Electronic health record data from patients diagnosed with CT/NG during 2018-2019 were analyzed. Treatment completion was defined as documentation of Centers for Disease Control and Prevention-recommended treatment ≤30 days after testing. Regression was used to assess differences in treatment completion across groups; analyses were stratified by birth sex. Most of the 2426 male (86%) and 754 (72%) female patients diagnosed with CT/NG completed treatment in ≤30 days; 74% of male and 36% of female patients were treated same-day. Among 890 male patients not treated same-day, treatment completion was associated with other same-day antimicrobial treatments (adjusted prevalence ratio, 0.76 [95% confidence interval, 0.61-0.94]), longer test processing times (≥10 days; 0.78 [0.65-0.95]) infection at multiple anatomic sites (1.49 [1.25-1.76]), and patients with previous clinic visits (1.16 [1.03-1.31]). Among 483 female patients not treated same-day, treatment completion was associated with diagnosis year (2019 vs. 2018; 1.23 [1.05-1.43]) and residential addresses 2 to 5 miles (vs. <2 miles) from clinic (1.25 [1.02-1.53]). Demographic and behavioral characteristics were not associated with treatment completion. Substantial proportions of male and female sexual health clinic patients did not complete treatment. Our findings underscore the need for implementation of highly sensitive and specific point-of-care (POC) CT/NG testing to improve treatment completion in this setting.